The Impact of Media and Monotoring on Corruptin in Decentralized Public Programs: Evidence from Madagascar - Nathalie Francken; Bart Minten; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
Local capture of public expenditures is an important problem for service delivery and poverty reduction in developing countries. Standard anticorruption institutions may not be effective, as these tend often to be corrupt themselves. This paper analyses the impact of monitoring and infirmation distribution through the mass media on local capture of public expenditures on education in Madagascar in 2002-2003. We use survey data to assess capture in both cash and in-kind programs, at district and at school level. We find that local capture can be successfully constrained through a combination of monitoring and media programs. In addition to monitoring by the beneficiaries ('from below?, central monitoring ('from above? is important. More transparent funding mechanisms and access to mass media reduce capture. However, the impact of the media is conditional on the characteristics of the population. In communes characterized by high illiteracy, the impact of newspaper and poster campaigns is limited, and radios are more important to reduce capture.
Keywords: 330; Öffentliche Bildungsausgaben; Projektbewertung; Korruption; Kommunikationsmedien; Madagaskar